Progress on neuromodulation for treatment of rare movement disorders - DONG Wen⁃wen; QIU Chang; XU Yi⁃chen; YANG An⁃chao; ZHANG Wen⁃bin (Chinese Journal of Contemporary Neurology and Neurosurgery)
Traditional pharmacological treatments for rare movement disorders have limited efficacy. However, the emergence of neuromodulation technique such as deep brain stimulation (DBS), spinal cord stimulation (SCS), transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS) and electroconvulsive therapy (ECT) offers new hope for patients with rare movement disorders. This review systematically summarizes the application and efficacy of both invasived and non⁃invasived neuromodulation techniques in treating various rare movement disorders, including spinocerebellar ataxia (SCA), Huntington's disease (HD), and neuroacanthocytosis (NA), etc.. The aim is to provide guidance for the application of neuromodulation technique in rare movement disorders.